Migration and Pension - Sadka, Efraim; Razin, Assaf (Washington, D.C. : International Monetary Fund, 1998)
Migrants, being relatively low earners, are net beneficiaries of the welfare state. However, this paper uses a dynamic model to show that because of migrants' positive influence on the pension system, which is an important pillar of any welfare state, migration could be beneficial to all income (high and low) and age (old and young) groups.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet